The role of scouting activities in promoting patriotism for secondary school students – Iraq. - Abdul Hussein Ali Al-Farjawi, Ali; Jameel Abbas Al-Karawi, Haidar; Hamza Najm Al-Khafaji, Tahseen (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to identify the role of scouting activities in promoting patriotism among secondary school students in Iraq. The researchers used the descriptive approach in a survey method as it is appropriate to the nature of the study. The research sample was chosen randomly; 125 students practicing scouting activities; the school scouting team and 125 students not practicing scouting activities. The researchers used the patriotism scale as a tool to collect data. The results of the present study confirm the superiority of students practicing scouting activities over students not practicing scouting activities in patriotism and national affiliation.